Karakterisasi Senyawa Minyak Atsiri Ekstrak Etil Asetat Bawang Putih (allium sativum l.) - Taupik, Muhammad; Andy Suryadi, A. Muâ€™thi; Hiola, Faramita; Rannu, Jumriani (Indonesian Journal of Pharmaceutical Education, 2021)
Garlic (Allium sativum L.) is one of tuber vegetable crops that is widely grown in various countries in the word and is often used as food spices and medicines. The purpose of this study was to characterize the volatile oil compound ethyl acetate extract of garlic (Allium sativum L.) using Uv-Vis and IR spectrophotometric metods. Several methods used in this research included extraction, identification of compounds, fractionation, thin layer chromatography, prepative thin layer chromatography, and characterization of compounds using Uv-Vis spectrophotometry and IR spectrophotometry. A total of 3000 grams od garlic was macerated using 70% ethanol, then evaporated and obtained a thick extract of 421.5 grams. The results of thin layer chromatography used an eluent ratio of Methanol : Ethyl Acetate (4:2) obtained stains with an Rf value of 0,55. The optimizion result of maximum wavelength of garlic isolated (Allium sativum L.) is 232 nm wich indicated  the presence of an electron transition  nâ†’Ïƒ*.The results of IR  spectrophotometry had fuctional groups at wave numbers 3231.530 cm-1 (N-H), 1637.48 cm-1 (C=O), 1014.65 cm-1(C-N).